ANALYSIS OF ANTHROPONYMS IN THE MANUSCRIPT «QISSA-YI DJENKNAME-YI RISALE-YI SHAH-I MERDAN» - Kairanbayeva, N.; Shadkam, Z.; Demir, N. (Journal of Oriental Studies, 2022)
The names of lands and waters, the names of people are a mirror of the culture, customs, beliefs, worldview of a certain people. Among them, anthroponyms are a valuable heritage in the study of the history of the language, culture of the nation. Literary anthroponyms are the main branch of anthropo- nymics that requires important research. Especially among the medieval Turkic inscriptions that have survived to the present day, there are characters important to both history and literature. The article deals with the role and analysis of anthroponyms in the heroic poem about Hazrat Ali written at the beginning of the twentieth century. The object of the study is the religious manuscript “Kissa-i Jenkname-i Risale-i Shah-i Merdan”, writ- ten in the postclassical Chagatai language. Exploring the anthroponymic space of this text, we divided anthroponyms into historical and mythological characters. In our work, we consider the identification of proper names in the anthroponymic space of the manuscript. Among them there are historical characters such as the Prophet Muhammad (peace be upon him), His family and companions, and the mythological characters of Indian (Firuz Shah), Persian (Jam- shid Shah) and Chinese (Salsal Shah) legends as well. Key words: proper nouns, anthroponym, religious epic, Hazrat Ali, Chagatai language.